2023
DOI: 10.1101/2023.11.20.567970
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Staphylococcus aureusskin colonization is mediated by SasG lectin variation

Krista B. Mills,
Joseph J. Maciag,
Can Wang
et al.

Abstract: Staphylococcus aureuscauses the majority of skin and soft tissue infections, but this pathogen only transiently colonizes healthy skin. However, this transient skin exposure enablesS. aureusto transition to infection. Initial adhesion ofS. aureusto skin corneocytes is mediated by surface protein G (SasG). Here, phylogenetic analyses reveal the presence of two major divergent SasG alleles inS. aureus, SasG-I and SasG-II. Structural analyses of SasG-II identified a unique non-aromatic arginine in the binding poc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 63 publications
(136 reference statements)
0
3
0
Order By: Relevance
“…We also included strains that expressed a truncated form of SasG such as those of USA300 strain LAC and USA100 strain N315. Together, these strains represent different subtypes of SasG that have been recently described ( 49 ). Finally, we included strains lacking a copy of the sasG gene altogether, such as USA200 strains MN8 and MRSA252, as controls for comparison.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…We also included strains that expressed a truncated form of SasG such as those of USA300 strain LAC and USA100 strain N315. Together, these strains represent different subtypes of SasG that have been recently described ( 49 ). Finally, we included strains lacking a copy of the sasG gene altogether, such as USA200 strains MN8 and MRSA252, as controls for comparison.…”
Section: Resultsmentioning
confidence: 90%
“…We also found that there is significant variation in sasG expression and molecular characteristics among strains. It was recently reported that most S. aureus strains have a full-length copy of SasG ( 49 ), but not all express SasG at detectable levels ( 57 ) and some strains have truncated copies of SasG. USA400 MW2 and 502a encode full-length, surface-attached copies of SasG with 5 B-repeats which aggregate with high efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation